Diagnosis, Treatment and Follow Up of Acute Pulmonary Embolism: Consensus Practice from the PERT Consortium. (10th June 2019) - Rivera-Lebron, Belinda; McDaniel, Michael; Ahrar, Kamran; Alrifai, Abdulah; Dudzinski, David M.; Fanola, Christina; Blais, Danielle; Janicke, David; Melamed, Roman; Mohrien, Kerry; Rozycki, Elizabeth; Ross, Charles B.; et al.
Pulmonary embolism (PE) is a life-threatening condition and a leading cause of morbidity and mortality. There have been many advances in the field of PE in the last few years, requiring a careful assessment of their impact on patient care. However, variations in recommendations by different clinical guidelines, as well as lack of robust clinical trials, make clinical decisions challenging. The Pulmonary Embolism Response Team Consortium is an international association created to advance the diagnosis, treatment, and outcomes of patients with PE. In this consensus practice document, we provide a comprehensive review of the diagnosis, treatment, and follow-up of acute PE, including both clinical data and consensus opinion to provide guidance for clinicians caring for these patients.